The level of satisfaction of psychological needs based on the realistic model and its relationship to psychological happiness among An-Najah National University students - Kahla, Mays Majed; Nazzal, Filasteen Ismail (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the level of satisfying psychological needs among An-Najah National University students based on the realistic model, and to identify the level of psychological happiness among An-Najah National University students, in addition to knowing the relationship between satisfying psychological needs and psychological happiness among An-Najah National University students. The study used the descriptive correlative approach. The randomly chosen sample of the study was 209 male and female students. To collect the data the Psychological Needs Scale, according to the Realistic Model and the psychological happiness Scale were used. The study found that the level of satisfying psychological needs according to the realistic model among the students of An-Najah National University, according to the domain of survival, was medium, and that they had psychological happiness with a high degree. There is also an effect of psychological needs on the psychological happiness of An-Najah National University students. The results also showed that there were statistically significant differences in the degree of satisfying psychological needs based on the realistic model and its relationship to psychological happiness among university students, according to the college variable, in favor of the students of the College of Humanities. In light of the results, the study came out with a recommendation, including: Motivating university students to cooperate with each other and with the academic staff, including their educational and psychological interest, through cooperative education and workshops.